XVIII. asırda Anadolu’ da tasavvuf - Muslu, Ramazan (My University, 2002)
XVIII. Asırda Anadolu'da Tasavvuf adlı doktora tez çalışması, MÜ. İlâhiyat Fakültesi Tasavvuf tarafından planlanan Osmanlı'da Tasavvuf adlı projenin bir parçasıdır. Bu çalışmanın gâyesi, Osmanlı Tasavvuf Tarihi ile ilgili yapılacak detay çalışmalara ışık tutması ve bir alt yapı teşkil etmesidir. Girişte Kaynaklar tanıtıldıktan sonra, XVIII. asırda Osmanlı Devleti'nin Siyâsî, Sosyal, İktisâdî ve Kültürel durumu kısaca özetlenmiştir. Birinci Bölümde bu asırda Anadolu'da tasavvuf kültürünü yayan 800 civarında meşâyıhın 185 tekkedeki faaliyetleri üzerinde durulmuş ve mensup oldukları Halvetîlik, Nakşbendîlik, Mevlevîlik, Kadirîlik, Celvetîlik, Bektâşîlik, Bayrâmîlik, Sa'dîlik, Rifâîlik ve Bedevîlik gibi tarikatlar hakkında da kısaca bilgi verilmiştir. Özellikle bu asırda Halvetîliğe bağlı olarak, Cerrâhîlik, Sezâîlik, Salâhîlik, gibi yeni doğan tarikat kolları üzerinde de durulmuştur. İkinci Bölümde devlet ricâli, ulemâ ile meşâyıhın münasebetleri üzerinde durulmuş, ayrıca meşâyıh-meşâyıh münâsebetine de yer verilmiştir. Sonuç kısmında ise ulaşmış olduğumuz neticeler verilmiştir.

This thesis studies the sufi movements in 18th century in Anatolia. It's a part of on going study by the Marmara University, Fakulty of theology, Department of Sufism as to the complete history of sufism in Ottoman Lands. This study covers a short study of sufi movement in 18th century and aims to prepare foundations for more detailed researches. This study covers more than 800 sufi masters who lives in this period. The introduction chapter studies the social, culturel, economical and architectural life in 18th century. In addition to these, the sources used have been analyzied. The first chapter studies the Sufi Orders and Sufi Masters as well as the sufi lodges. The sufi orders studied are as follows: Halwatiyya, Naqshbandiyya, Mawlawiyya, Qadiriyya, Jalwatiyya, Baktashiyya, Bayramiyya, Sadiyya, Rifaiyya and Badawiyya. The study also includes the sub-branches that appeared in this century such as Jarrahiyya, Sezaiyya, Salahiyya which are sub-branches of Halwatiyya order. The number of sufi lodges which were active in this period is close to 185. The second chapter deals with the realitionship between the Ottoman Sultans and the Sufi Masters. This chapter also deals with realitionship between the Sufi Masters and scholors of Islamic Science and studies the social status of Sufi Masters and their relationship with the public. The conclusion chapter gives on overall evalatuation and analysis of our finding.
Keywords: Akâid ve Kelâm; Din; Islam Dini Tasavvuf; İslam Dini; Tasavvuf